Anatomic and radiographic study of the chin spine area of the mandible. Part I. Macro anatomical and radiological examination (LLC "Endo Press", 2020)
In the article considered the anatomic and radiological points of view on the lingual part of the mental region on the mandible. It is shown that in the field of mental spine on the mandible depending on type of a skull contains both the pronounced, and hardly noticeable channels having continuation in a jaw. According to radiological pictures presented the original classification of channels of a mental spine.